New Technologies for Teaching Mathematics in Basic Secondary School - Sikorskyi, Petro (Pedagogical Discourse, 2022)
The scientific article considers the current problems of the secondary school reform, in particular its second level – basic secondary education. The first stage of education reform is coming to an end in the primary school. A lot of financial resources have been invested to strengthen its educational and material base, didactic support, and retraining of teachers. The question arises, on what basis to continue to implement the basic pedagogical ideas of the concept of «New Ukrainian School» in basic secondary school? There will be new model curricula, textbooks and teaching aids. However, the established new content of education must be mastered as fully as possible with pupils during classes. This requires not only new pedagogical approaches, but also new learning technologies. Obviously, the classroom system will continue to dominate, which has many drawbacks. We analyze in the article analyzes its main shortcomings in order to significantly improve it. To do this, various definitions of the concept of «educational technology» are analyzed, common and distinctive features are identified and, based on this, it is given a strict definition. The main components of educational technology are the subjects of learning (pupils and teachers), content, techniques and methods, forms and means of learning. Depending on their role in teaching pupils, different learning technologies and contexts of the classroom learning system can be modeled. Analyzing the effectiveness of teaching mathematics in the educational process in the primary school, the author seeks ways to ensure continuity in the education of pupils of 4th and 5th grades, how to quickly adapt the primary school graduates to new learning conditions in 5th grade and more. The effectiveness of students’ learning in primary school is characterized by the following indicators: formed intellectual tools (observation, memory, thinking, attention, imagination, etc.), general learning skills (speaking, writing, reading) and acquired basic knowledge. Successful learning of students in basic secondary school will largely depend on this. Based on this, there are ways to improve the educational process in primary school and adapt it to the principle of modularity in grades 5-6.